Physical Space Elements in Outdoor Comfort of Urban Kampung in Jakarta - Inavonna; Cut Sannas Saskia; Fajar Rezandi; Arief Fadhilah (Talenta Publisher, 2026)
The character of urban villages is uniquely distinctive, where the physical conditions of these areas develop organically as a manifestation of the local wisdom and lifestyle of the community. This spontaneous spatial formation reflects the community's interaction with its surroundings, which, in turn, affects comfort levels, especially in outdoor spaces that play a crucial role in daily activities. This study focuses on exploring the physical factors that influence physiological comfort in the outdoor spaces of urban villages, with a case study in Petamburan Sub-district, Central Jakarta. The research employs a quantitative approach, gathering data through physical measurements and direct observations of outdoor spaces. The collected data is analyzed using linear regression in SPSS 25 software to identify and understand the relationship between spatial elements and the level of comfort perceived by the community. The study identifies key physical elements contributing to physiological comfort, including the ratio of distance to the height of spatial boundaries and the percentage of roofing coverage. These findings are expected to provide a deeper understanding of the role of physical elements in creating physiologically comfortable spaces, ultimately supporting the design of outdoor spaces in urban villages to be more conducive to community activities and sustainability.